Incidence of and risk factors for cryptococcosis in kidney transplant recipients in Taiwan—A nationwide population-based study. (November 2019) - Chen, Yung-Tai; Lee, Wen-Sen; Tsai, Che-An; Fan, Wen-Chien; Wu, Ping-Feng; Wang, Fu-Der
Highlights: Kidney transplant recipients had a higher risk of cryptococcosis, especially involving the CNS. Cumulative rates of cryptococcosis from KTRs continued to increase steadily postoperatively. Being older or having cancer in KTRs were found to be independent risk factors for cryptococcosis. Abstract: Objectives: The aim of this study was to determine the long-term incidence of cryptococcosis in kidney transplant recipients (KTRs) and to analyze its risk factors. Methods: This retrospective population-based cohort study analyzed data obtained from Taiwan's National Health Insurance Research Database for KTRs during 2000–2012 and matched cohorts. Both populations were followed until death, development of cryptococcosis, or December 2013. Results: A total of 4, 933 KTRs and 49, 930 matched patients were included. The cryptococcosis incidence rates for the KTR cohort and matched cohort were 10.59 and 0.4 per 10, 000 person-years, respectively. The hazard ratio for cryptococcosis among KTRs was 26.65 ( p  < 0.001); and 43.77 ( p  < 0.001) for cryptococcosis affecting the central nervous system (CNS). The Kaplan-Meier method confirmed an elevated cumulative incidence of cryptococcosis among KTRs (1.00% vs. 0.04%). Predictors for cryptococcosis were advanced age (OR 1.39, 95% CI 1.02–1.89, P  = 0.038) and cancer (OR 2.63, 95% CI 1.22–5.67, P  = 0.013), but not the use of any particular class of immunosuppressants. Conclusions: KTRs are at dramatically higher risk of developing cryptococcosis, especially with CNS involvement, relative to a non-KTR matched cohort. Older KTRs and those with cancer are at even higher risk of developing cryptococcosis.